Economics of Digital Learning and Artificial Intelligence in Higher Education: Impact on Library Use and Student Achievement in Urban Nepal - Bishwakarma, Sagar; Bista, Smeeth (Journal of Innovation in Academia, 2025)
This study examines the economic relationship between traditional academic resources and digital learning tools, including generative artificial intelligence (AI), among higher education students in Kathmandu, Nepal. Using cross-sectional data from 439 urban students and an ordered logistic regression framework, the study tests substitution and complementarity effects. Results show that e-learning platforms significantly substitute for physical library visits, reflecting reduced transaction costs, while also enhancing academic performance and research participation. In contrast, generative AI use shows no significant association with library demand or academic outcomes, indicating an early stage of adoption. Core library services continue to deliver distinct benefits and cannot be fully replaced by AI or digital tools. The findings support an integrated policy approach that combines strategic investment in library infrastructure and staff quality with the promotion of high-impact e-learning platforms and ethical AI tools to strengthen academic achievement, research engagement, and human capital development.